Feminism(s) and the law. Old legacies and new challenges (2017)
In the ongoing debate on the health of feminism, some authors accuse “second wave” feminists, especially European “feminists of difference”, of having weakened fem¬inist claims by abandoning the emancipatory inspiration of “first wave” feminism. “Sec¬ond wave” feminists are also accused of overlooking the importance of the law. If we delve deeper, however, their perspective on law appears to represent one of their most important legacies. Abandoning it in favor of an acritical enthusiasm for liberal gender mainstreaming or a gendered “politics of identity” would be a mistake. Today’s femi¬nists should instead work to adapt this legacy to contemporary challenges.